2014
DOI: 10.1038/labinvest.2014.123
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic roles of Bmi1 and its therapeutic inhibition by histone deacetylase inhibitor in tongue cancer

Abstract: The polycomb complex protein Bmi1 (B lymphoma Mo-MLV insertion region 1 homolog) mediates epigenetic transcriptional silencing by modifying chromatin structure and is critical for stem cell homeostasis and tumorigenesis. Bmi1 is frequently overexpressed in human malignancies and therefore has key diagnostic and prognostic significance, and holds potential as a therapeutic target. Here we sought to characterize the expression patterns and oncogenic roles of Bmi1 in tongue squamous cell carcinoma and to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 56 publications
2
80
0
2
Order By: Relevance
“…This led us to study the effect of sodium butyrate on breast cancer cell growth and explore the possible involvement of 15-Lox-1 in the pathway that sodium butyrate applies to regulate breast cancer cell growth. Our results have shown that the percentage of viable cells was reduced following treatment with increasing concentration of sodium butyrate which is consistent with the effect of sodium butyrate on tongue (Li et al 2014), pancreas (Natoni et al 2005), and prostate (Paskova et al 2013). Accordingly, the sodium butyrate-induced cell death was significantly abrogated upon pretreatment with 15-Lox-1 inhibitor in MCF-7 and MDA-MB-468.…”
Section: Discussionsupporting
confidence: 88%
“…This led us to study the effect of sodium butyrate on breast cancer cell growth and explore the possible involvement of 15-Lox-1 in the pathway that sodium butyrate applies to regulate breast cancer cell growth. Our results have shown that the percentage of viable cells was reduced following treatment with increasing concentration of sodium butyrate which is consistent with the effect of sodium butyrate on tongue (Li et al 2014), pancreas (Natoni et al 2005), and prostate (Paskova et al 2013). Accordingly, the sodium butyrate-induced cell death was significantly abrogated upon pretreatment with 15-Lox-1 inhibitor in MCF-7 and MDA-MB-468.…”
Section: Discussionsupporting
confidence: 88%
“…26 The gene-specific primers for human PKM2 and GAPDH were used as previously reported. 13,26 Relative mRNA expression was calculated as compared to GAPDH using comparative CT method.…”
Section: Rna Extraction and Real Time Rt-pcrmentioning
confidence: 99%
“…16,26 Immunohistochemical staining for PKM2 was performed on 4-mm formalin-fixed, paraffin-embedded tumor specimens. Briefly, tissue sections from representative paraffin blocks were deparaffinised and rehydrated.…”
Section: Histopathological Evaluation and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Polycomb group proteins (PcG) are critical transcriptional repressors that epigenetically modify chromatin and contribute to cell fate, stem cell self-renewal and cancer development (52,53). B lymphoma Mo-MLV insertion region 1 homolog (Bmi1) is the core member of the polycomb repressive complex 1 (PRC1), one of two PRCs in PcG (53).…”
Section: Genetic Silencing and Pharmacological Inhibition Of Bmi1 As mentioning
confidence: 99%